Cooling of the heated circular porous disc with a circular jet - Gürtürk, Mert; Öztop, Hakan Fehmi (My University, 2019)
In this study, an experimental analysis has been performed on jet impingement ontoclose-cell porous material which is the shape of a circular porous disc which is aluminum foam.This porous material was located on the circular heater and temperature distribution, local andaverage Nusselt number were observed at the different situations. Experiments were carried outby considering different parameters which are Reynolds number (1048, 2620, 4192), thethickness of porous disc (6, 8, 10 mm) and heater power (3.6, 6.8, 10.5 W). The results showthat the maximum average Nu number value is calculated as 464.06 at Re = 4192, P = 10.5 W.It is observed that for the lowest average Nu number value is obtained at P = 3.6 W and Re =1048 for without porous material. The lowest average Nu number value is calculated as 94.201.It is found that the porous materials can be used to control heat transfer.
Keywords: Bahçe Bitkileri; Gıda Bilimi ve Teknolojisi